Differential methylation of the micro‐RNA 7b gene targets postnatal maturation of murine neuronal Mecp2 gene expression. Issue 4 (9th December 2013) - Chen, Yongjun; Shin, Bo‐Chul; Thamotharan, Shanthie; Devaskar, Sherin U.
ABSTRACT DNA methylation and microRNAs (miRNAs) play crucial roles in maturation of postnatal mouse neurons. Aberrant DNA methylation and/or altered miRNA expression cause postnatal neurodevelopmental disorders. In general, DNA methylation in the 5′‐flanking region suppresses gene expression through recruitment of methyl‐CpG binding domain proteins (MBPs) to the cytosine residues of CpG dinucleotides. X‐linked MeCP2 (methyl‐CpG binding protein 2), a member of MBPs, is a methylation‐associated transcriptional repressor with other functions in the central nervous system (CNS). miRNAs negatively regulate gene expression by targeting the 3′‐untranslated region (3′UTR). Some miRNA genes harboring or being embedded in CpG islands undergo methylation‐mediated silencing. One such miRNA is miR‐7b which is differentially expressed through stages of neurodevelopment. In our present study, we focused on a canonical CpG island located in the 5′‐flanking region of the murine miR‐7b gene. Hypermethylation of this CpG island down‐regulates miR‐7b while recruiting MeCP2 to the methylated CpG dinucleotides. Meanwhile, Mecp2, a target of miR‐7b, was up‐regulated due to lack of restrain exerted by miR‐7b during maturation of postnatal (PN) mouse neurons between PN3 and PN14. Our results indicate that miR‐7b is a direct downstream gene transcriptional target while also being a negative post‐transcriptional regulator of Mecp2 expression. We speculate that this bidirectional feed‐back autoregulatory function of miR‐7b and Mecp2 while linking DNA methylation and miRNA action maintains the homeostatic control of gene expression necessary during postnatal maturation of mammalian neurons. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 74: 407–425, 2014